Board of Editor - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2020)
Board of Editor PATRON:               Dean - Faculty of Civil, Environmental, Earth Sciences - ITS.Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE                  :   Head of Department  – Civil Engineering Department - ITSBOARD OF EDITOR               Chief Editor                       :   Hitapriya Suprayitno             ITS, Indonesia                    h-index (GS =   8)Editor                               :   Ria Asih Ariyani Soemitro       ITS, Indonesia                   h-index (GS =   9)                                            Data Iranata                         ITS, Indonesia                   h-index (GS =   3)                                              Alex Abdi Chalik                    PUPR, Indonesia                 h-index (GS =     )                                             Danang Parikesit                   UNIID, Indonesia                h-index (GS =   7)                                            Maimunah Sapri                    UTM, Malaysia                    h-index (GS = 14) Address                           :     Editor JIFAM – Room  J - 201                                             Departement of Civil Engineering                                                        Institut Teknologi Sepuluh Nopember                                             ITS Campus, Sukolilo, Surabaya 60111                                             Email: jurnal.jifam@gmail.com                                               Website: https://iptek.its.ac.id/index.php/jifamReviewer for this EditionRia Asih Aryani Soemitro, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Data Iranata, Institute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Caroline Sutandi, Universitas Parahyangan, Bandung, Indonesia.Eko Budi Santosa, Instiute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Akhmad Wicaksono, University of Brawijaya, Malang, Indonesia.Hitapriya Suprayitno, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.